Geochemical Mass Balance and Elemental Transport during the Weathering of the Black Shale of Shuijingtuo Formation in Northeast Chongqing, China - Sixiang Ling; Xiyong Wu; Siyuan Zhao; Xin Liao; Yong Ren; Baolong Zhu (The Scientific World Journal)
An understanding of the processes that control the behavior of major elements with respect to weathering profile is essential to calculate the mobility, redistribution, and mass fluxes of elements. Hence, this study aims to determine the geochemical mass balance, strain, elemental correlation, and transport in weathering profiles. We constructed three weathering profiles for the black shale of Shujingtuo formation. As per the principal component analysis of major elements, density, and pH values, the first component represents the “elemental factor” and the second denotes the “external factor.” The “depletion” pattern is a mass transportation pattern, and Na, K, and Mg are depleted along transect relative to the composition of fresh rock. Fe is redeposited at the bottom half of the saprock zone, whereas Al is accumulated at the regolith zone. The Fe and Al patterns are attributed to the “depletion–addition” and “addition” patterns, respectively. The strain in profiles A and B demonstrates the expansion at the regolith zone and part of the saprock zone. In profile C, however, these zones collapsed at all depths. In chemical weathering, Na, K, Ca, Mg, and Si are depleted in the following order: valley (C) > near mountaintop (B) > ridge (A).